Transnational Education in Malaysia: Development, Challenges, and Strategic Alignment - Sia, Joseph; Jimmie, Anita (IGI Global, 2023)
Private higher education in Malaysia has undergone radical transformations with the aim of becoming a regional hub for higher education in Southeast Asia, and to transform the country into one that has a fully developed knowledge-based economy. To understand this transformation, the purposes of this chapter are to identify key prospects and challenges of international branch campuses (IBCs) and propose strategic alignment on the operation and administration of the IBCs in Malaysia. In order to identify and understand the challenges IBCs face when operating in Malaysia, this study adopts a review approach that is supported by findings and from academic and grey literature. The results of this review indicate that IBCs are faced with complex challenges and are on unequal footing with other local universities. This chapter uncovers various demanding issues and discusses strategic alignment of IBCs. Limitations and recommendations for future research are also incorporated in this chapter.